2013
DOI: 10.4081/ni.2013.e16
|View full text |Cite
|
Sign up to set email alerts
|

A score based on screening tests to differentiate mild cognitive impairment from subjective memory complaints

Abstract: It is not easy to differentiate patients with mild cognitive impairment (MCI) from subjective memory complainers (SMC). Assessments with screening cognitive tools are essential, particularly in primary care where most patients are seen. The objective of this study was to evaluate the diagnostic accuracy of screening cognitive tests and to propose a score derived from screening tests. Elderly subjects with memory complaints were evaluated using the Mini Mental State Examination (MMSE) and the Brief Cognitive Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…These findings are consistent with previous studies. 5 , 10 , 12 , 27 , 29 , 30 The mean VFT score in the present study was similar to that found in other studies evaluating healthy elderly adults. Performance on this test can be considered indicative of normal aging, for which it is highly sensitive in discriminating early stages of dementia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous studies. 5 , 10 , 12 , 27 , 29 , 30 The mean VFT score in the present study was similar to that found in other studies evaluating healthy elderly adults. Performance on this test can be considered indicative of normal aging, for which it is highly sensitive in discriminating early stages of dementia.…”
Section: Discussionsupporting
confidence: 91%
“… 6 , 28 This pattern of results contrasts with other studies. 17 , 29 With regard to age, no difference in functional capacity for instrumental activities was found between the age groups. However, an association was found between performance on activities of daily living and education.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, only one previous study has examined the accuracy of either MMSE, CDT, or AQT for identifying MCI and differentiating it from SCD [ 42 ]. In that study, 32 elderly with subjective memory complaints and 74 with MCI were recruited from community centers for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Scores were adjusted according to appropriate age and education norms. Additional details of the evaluation protocol used, and neuropsychological tests administered, are reported in de Gobbi Porto et al [ 20 ].…”
Section: Methodsmentioning
confidence: 99%